Benzene biodegradation by indigenous mixed microbial culture: Kinetic modeling and process optimization. (April 2017) - Padhi, Susant Kumar; Gokhale, Sharad
Abstract: Benzene is one of hazardous pollutants generated from paint, chemical, and petrochemical industries have a harmful impact on human health and the atmosphere. This study reports benzene biodegradation by indigenous mixed microbial culture in shake flasks over a concentration ranging from 25 to 600 mg/l, and the kinetics involved in the process has been modeled. Experimental data obtained were fitted to both inhibition and noninhibition models to determine the biokinetic constants. Haldane model was best to predict the experimental data. The central composite design was further used for optimization of pH and benzene concentration to enhance the benzene biodegradation. At an optimum pH of 7.05 and benzene concentration of 332.82 mg/l, the maximum estimated specific growth rate and degradation rate were 0.05 1/h and 6.01 mg/l h, respectively. The LC-MS analysis of sample indicate the presence of catechol, cis-1, 2-dihydrobenzene-1, 2-diol, and 2-hydroxymuconate semialdehyde as intermediates, which justifies the developed pathway of benzene biodegradation. The predominant microorganism in the mixed culture responsible for benzene degradation was later identified to be Enterobacter cloacae SG208. The results provide insight into the process of benzene biodegradation and prove the potential of indigenous mixed culture for treatment of benzene. Graphical abstract: Highlights: Haldane model was best to predict the biokinetic constants. CCD based on RSM was used for enhancing the benzene biodegradation. Intermediates produced confirms the developed pathway of benzene biodegradation. Enterobacter cloacae SG208 was identified as a predominant benzene degrading strain.